The art of Mesoamerica : from Olmec to Aztec / Mary Ellen Miller. - Miller, Mary Ellen. (World of art., 2006)
"Mary Ellen Miller surveys the artistic achievements of the high Precolumbian civilizations - Olmec, Maya, Teotihuacan, Toltec, Aztec - as well as those of their less well-known contemporaries. Their pyramids and palaces, jades and brightly colored paintings emerge from these pages as vividly as when they first astonished Cortes's men in 1519. The fourth edition of this standard work includes new discoveries, from Palenque, Mexico, where architecture and sculpture reveal a dramatic eighth century, to San Bartolo, Guatemala, where Maya murals of unprecedented complexity and sophistication have been uncovered in the past few years. Continuing hieroglyphic decipherments - not only of Maya writing but of other Mesoamerican civilizations - provide insights into works of the past."--Jacket.